Anthropometric profiles are associated with long-term career attainment in elite junior rowers: A retrospective analysis covering 23 years - Winkert, K.; Steinacker, J. M.; Machus, K.; Dreyhaupt, J.; Treff, G. (European Journal of Sport Science, 2019)
Introduction: Successful rowers are heavier and taller than their opponents, but the effect of these variables on long-term career attainment in juniors has not been examined. We therefore analysed this in a large sample of elite German junior rowers. Methods: Former German Junior National Team rowers (N = 910; 399 females) were grouped according to their highest career attainment, i.e., participation in U19-, U23-, Senior World Championships or Olympic Games (OG). Differences in standing height (SH), body mass (BM) and body mass index (BMI) between groups were analysed using unpaired t-tests and magnitude-based inferences (MBI), effects of anthropometrics on career attainment were analysed with a proportional odds model. Interquartile ranges of the OG group were used to define normative data ranges. Results: SH and BMI very likely differed between career attainment in females. The same was found in males for SH and BM. BM (odds ratio (OR) = 0.958, P = .0171) and BMI (OR = 0.787, P = .0004) had a significant effect on career attainment in females as SH (OR = 1.072, P = .0002) and BM (OR = 1.049, P = .0004) had in males. Interquartile ranges of SH and BM were 178-184 cm and 68-73 kg in females, 190-196 cm and 84-93 kg in males. Conclusion: Anthropometric characteristics at junior age affect long-term career attainment even within elite U19 National Team rowers, underlining the relevance of anthropometric assessments and their consideration for talent identification and development programmes in rowing. We provide evidence-based normative data that rule out an anthropometric limitation of junior rowers for career progression to Olympic level.